Towards sustainability of fisheries in the food retail - Almeida, I. D. de.; Silva, J. M. V.-B. da.; Harjivan, C. M. K. (Proceedings of 20th EurOMA - Operations Management at the Heart of Recovery, 2013)
Socially acceptable practices and ecological concern are major pressures driving organisations towards sustainable operations. Retailers play vital roles promoting responsible consumption and leading supply chain (SC) partnerships. This research has succeeded to introduce fish traceability and ecolabelling, despite the SC approach being at an early stage. Suppliers lacking confidence and trust, CPFR absence and, consumers needing briefing/sensibilization to align behaviour towards fish species in risk, capture methods and aquaculture alternatives were research findings concerning weaknesses to address in future. Research contribution: retailer action in SC, leading to certification and fish stock preservation and, retailer image improving accordingly to Greenpeace indicators.